2014
DOI: 10.1007/s13277-014-2456-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of methylenetetrahydrofolate reductase and methionine synthase polymorphisms with breast cancer risk and interaction with folate, vitamin B6, and vitamin B12 intakes

Abstract: We assessed the association between dietary intake of folate and the MTHFR genotype with breast cancer in a Chinese population, with additional analysis of the interactions of gene polymorphisms and dietary intake of folate, vitamin B6, and vitamin B12. A case-control study was performed, and 535 patients with newly diagnosed breast cancer and 673 controls were enrolled into this study. The MTHFR 667TT genotype (odds ratio (OR) = 1.82, 95 % confidence interval (CI) = 1.24-2.97) and T allele (OR 0= 1.48, 95 % C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 33 publications
(46 reference statements)
2
34
0
2
Order By: Relevance
“…Our results were similar to other studies addressing thyroid and breast cancers (Kotsopoulos et al, 2008;Kweon et al, 2014). For the MTR A2756G polymorphism, ours results have shown no association between this SNP and thyroid and breast cancers, which agreed with the results from 4 case-control breast cancer studies (Naushad et al, 2011;He et al, 2014;Jiang-hua et al, 2014;Weiwei et al, 2014). Meta-analyses by Zhong et al (2013) and Weiner et al (2012) also found no association between MTR A2756G polymorphism and breast cancer development.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results were similar to other studies addressing thyroid and breast cancers (Kotsopoulos et al, 2008;Kweon et al, 2014). For the MTR A2756G polymorphism, ours results have shown no association between this SNP and thyroid and breast cancers, which agreed with the results from 4 case-control breast cancer studies (Naushad et al, 2011;He et al, 2014;Jiang-hua et al, 2014;Weiwei et al, 2014). Meta-analyses by Zhong et al (2013) and Weiner et al (2012) also found no association between MTR A2756G polymorphism and breast cancer development.…”
Section: Discussionsupporting
confidence: 93%
“…Both studies included men and women. In a breast cancer case-control study conducted in Chinese women, an increased risk for cancer development was found in those carrying the 677TT genotype (He et al, 2014;Jiang-hua et al, 2014;Weiwei et al, 2014). These results were all in agreement with our present findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TYMS 3′-UTR ins6/del6 showed positive association with breast cancer in the Japanese population (Zhai et al 2006), while it showed a null association in Indians (Naushad et al 2011), Chinese (Zhai et al 2006) and Germans (Justenhoven et al 2005). MTHFR C677T is the most widely studied polymorphism of this pathway; the segregation of data based on ethnic group or populations revealed a strong association of this polymorphism in Turkey (Deligezer et al 2005;Ozen et al 2013), China (Cheng et al 2008Gao et al 2009;Wu et al 2012;Jiang-Hua et al 2014), Syria (Lajin et al 2012), Morocco (Diakite et al 2012), and North America (Maruti et al 2009;Bentley et al 2010;Ramos-Silva et al 2015). Two studies, i.e., one on multi-ethnic group (Le Marchand et al 2004) and another on the Iranian population (Hosseini et al 2011), showed a protective role of this polymorphism.…”
Section: Introductionmentioning
confidence: 99%